Valuers' strategies for coping with the dearth of market data in two Nigerian cities: Ibadan and Abeokuta. (3rd May 2016) - Ashaolu, T. A.; Olaniran, M. O.
Abstract: Access to and analysis of data, especially market-related data, remains central to professional valuation. This paper examines the ease of eliciting market data for valuation purposes by valuers in the residential property sector and the reaction to the dearth of data among valuers in the two south-western Nigerian cities of Ibadan and Abeokuta. A five-point Likert-type scale was used to measure respondents' disposition towards alternative data sources with the results analysed using weighted mean score and logit regression. The study revealed that rental value and comparable sales price were most easily accessed with the greatest challenge being to access property yields and appropriate rates of depreciation. Given the difficulties in accessing data, it was found that valuers in the study area either make recourse to colleagues, shift to the next available method or adopt various alternative data-scooping measures, with years of practical experience, position in the firm and professional status exerting considerable influence on decisions. The paper suggests the establishment of a centralized databank for Nigerian valuers and a requirement for them to maintain a logbook of valuation computations with records of data used to justify otherwise inexplicable valuations, with further research into the interpretation and derivation of yields among Nigerian valuers recommended.